Mutant Cu/Zn Superoxide Dismutase (A4V) Turnover Is Altered in Cells Containing Inclusions - Farrawell, Natalie E.; Yerbury, Justin J. (Frontiers in Molecular Neuroscience, 2021)
SOD1 mutations account for 20% of familial amyotrophic lateral sclerosis (ALS) cases in which the hallmark pathological feature is insoluble SOD1 aggregates within motor neurons. Here, we investigated the degradation and synthesis of mutant SOD1 to determine whether the aggregation of mutant SOD1A4V affects these processes. We confirm that, in general, the degradation of mutant SOD1A4V occurs at a significantly faster rate than wild-type SOD1. We also report that the turnover and synthesis of mutant SOD1A4V is impaired in the presence of insoluble SOD1A4V aggregates. However, the timing of aggregation of SOD1A4V did not coincide with UPS dysfunction. Together, these results reveal the impact of SOD1 aggregation on protein degradation pathways, highlighting the importance of the UPS in preventing neurodegenerative disorders such as ALS.